Pengaruh Promosi dan Persepsi Masyarakat terhadap Minat Menabung Produk Tabunganku pada Bank Sinarmas Kabupaten Mamuju - Muh. Syahrul (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2024)
This study aims to examine the influence of promotion and community perception on the interest in saving the Tabunganku product at Bank Sinarmas in Mamuju Regency. Effective promotion through various media, both print and digital, is believed to affect the public's interest in choosing saving products. In addition, public perception regarding service quality, facility prices, and the credibility of the bank also plays a significant role in the decision to save. Using both qualitative and quantitative approaches, this research collects data through surveys and interviews with Bank Sinarmas customers. The results show that both the promotion carried out by Bank Sinarmas and the community’s perception of the bank's service quality and facilities significantly influence the interest in saving the Tabunganku product. These findings are expected to provide insights for the bank to improve promotional strategies and understand the importance of community perception in attracting customers.